Transformation of accreditation of higher education in health in Indonesia: qualitative assessment - Moenadjat, Yefta; Tunru, Insan Sosiawan A.; Soemardjo, Sutrisno (UI Scholars Hub, 2024)
Accreditation of higher education in health in Indonesia shifts to the qualitative assessment driven to ensure quality improvement. The method replaces the former quantitative assessment method that has been applied since 2012; it will be effective in January 2025. The driving factors and rationale of transformation are outlined in this article. The rationale of the qualitative assessment that applies principle–based accreditation and the quantitative assessment that applies rule–based accreditation is reviewed here. Information on the accreditation procedure and the goal is presented, aiming for institutions to prepare for this new version of accreditation.